2019
DOI: 10.11591/ijere.v8i4.20294
|View full text |Cite
|
Sign up to set email alerts
|

The preliminary study on inverted problem-based learning in biology among science foundation students

Abstract: <span>The emergent of Science, Technology, Engineering and Mathematics (STEM) Education in Malaysia has embarked challenges in higher education system. Conventional teaching methods often cause lower learning gain, fear and bad perceptions among students. The old initiative may also be the cause of students’ demotivation, lower interest in learning a subject or even dropouts. This study was conducted to evaluate the effectiveness of an inverted classroom by using the problem-based method in Biology subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Sumen and Calisici (2016) found the skills of the elementary school teacher association through the science education program using STEM. The same finding in a different context is in Matawali et al (2019) that Biology learning carried out with PBL integrated with STEM approach increased students' scores who studied biology using the PBL model with the STEM approach.…”
Section: Figure 3 the Example Of Respondents' Drawing After Teaching Internshipmentioning
confidence: 53%
See 3 more Smart Citations
“…Sumen and Calisici (2016) found the skills of the elementary school teacher association through the science education program using STEM. The same finding in a different context is in Matawali et al (2019) that Biology learning carried out with PBL integrated with STEM approach increased students' scores who studied biology using the PBL model with the STEM approach.…”
Section: Figure 3 the Example Of Respondents' Drawing After Teaching Internshipmentioning
confidence: 53%
“…They argued that the application of STEM needs to be implemented in science learning in elementary schools. Likewise, Matawali et al (2019) also found that Biology learning carried out with PBL integrated with the STEM approach increased students' scores who studied biology using the PBL model with the STEM approach.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The major components of a problem solver to be; knowledge, heuristics, and metacognition [16], [17]. Whilst, knowing a problem is the first step to getting its solution [18]. When there is less basic knowledge and skills on the problem, the more the working memories are burdened [19].…”
Section: Introductionmentioning
confidence: 99%